2013
DOI: 10.1021/ml400432f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anti-HCV Activity of 4-Hydroxyamino α-Pyranone Carboxamide Analogues

Abstract: High genetic variability in hepatitis C virus (HCV), emergence of drug resistant viruses and side effects demand the requirement for development of new scaffolds to show an alternate mechanism. Herein, we report discovery of new scaffold I based on 4-hydroxyamino α-pyranone carboxamide as promising anti-HCV agents. A comprehensive structure−activity relationship (SAR) was explored with several newly synthesized compounds. In all promising compounds (17−19, 21−22, 24− 25, and 49) with EC 50 ranging 0.15 to 0.40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 26 publications
1
40
0
Order By: Relevance
“…We observed that when A and B both were phenyl, the compound was highly active with EC 50 0.35 µM. 7 However, substitution on A shown a tendency to decrease the anti-HCV potential of compounds irrespective of whether B is phenyl/substituted phenyl/alkyl/ alkanol/alkyl ester/benzyl. 4-hydroxyamino-α-pyranone carboxamide scaffold I and the scaffold for present investigation (II).…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…We observed that when A and B both were phenyl, the compound was highly active with EC 50 0.35 µM. 7 However, substitution on A shown a tendency to decrease the anti-HCV potential of compounds irrespective of whether B is phenyl/substituted phenyl/alkyl/ alkanol/alkyl ester/benzyl. 4-hydroxyamino-α-pyranone carboxamide scaffold I and the scaffold for present investigation (II).…”
mentioning
confidence: 82%
“…5,6 Therefore, novel therapies are invited for safer and more efficient treatment. In our previous investigation, 7 we had evaluated anti-HCV activities of new analogs based on 4-hydroxyamino-α-pyranone carboxamide (I, Fig. 1) with various combinations of A (phenyl/ substituted phenyl) and B (phenyl/substituted phenyl/alkyl/alkanol/alkyl ester/ benzyl).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The synthetic γ‐alkylidenebutenolide C displays an antibacterial activity with a minimum inhibitory concentration (MIC) value of 20 µ g/mL against Escherichia coli while γ‐alkylidenebutenolide D exhibits cytotoxic activity against Ec9706 cells . In addition, the α‐pyranone carboxamide E is reported as promising anti‐hepatitis C agent . These skeletal motifs also feature as intermediates for the synthesis of related heterocycles and complex natural products …”
Section: Introductionmentioning
confidence: 99%
“…The molecular data set selected for this study consists of 42 compounds with anti‐HCV (hepatitis C virus) activity, synthesized and characterized by Konreddy et al. (). Hepatitis C virus is a single‐stranded RNA virus that belongs to the Flaviviridae family.…”
Section: Introductionmentioning
confidence: 99%